2010
DOI: 10.1177/104063871002200119
|View full text |Cite
|
Sign up to set email alerts
|

The Same Papillomavirus is Present in Feline Sarcoids from North America and New Zealand but Not in Any Non-Sarcoid Feline Samples

Abstract: Abstract. Feline sarcoids are uncommon dermal neoplasms that are associated with papillomavirus (PV) infection. A single PV type, designated feline sarcoid-associated PV (FeSarPV), was detected in 9 feline sarcoids from North America. As FeSarPV has only been detected within feline sarcoids, the epidemiology of the infection remains unknown. The present study used polymerase chain reaction (PCR) to investigate whether this PV is also present within sarcoids from New Zealand cats. Additionally, as PVs are often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 20 publications
3
43
0
Order By: Relevance
“…So far, feline sarcoids were reported in North America, New Zealand, England, Sweden and Australia (Schulman et al, 2001;Munday et al, 2010). These lesions resemble those described as equine sarcoids (Gumbrell et al, 1998;Schulman et al, 2001;Gross et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…So far, feline sarcoids were reported in North America, New Zealand, England, Sweden and Australia (Schulman et al, 2001;Munday et al, 2010). These lesions resemble those described as equine sarcoids (Gumbrell et al, 1998;Schulman et al, 2001;Gross et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…The entire genomic sequence of PVs involved in feline sarcoids (FeSarPV) isolated from cats was re cently published and classified as a Deltapapillomavirus. However, since DNA of this virus was also amplified from samples of normal skin and fibropapillomas of cattle (Munday et al, 2010;daSilva et al, 2012), it seems likely that feline sarcoids are due to crossspecies infec tion by BPVs (Schulman et al, 2001). …”
Section: Histologymentioning
confidence: 99%
“…7 However, in contrast to equine sarcoids in which recent studies have shown detection of BPV-1 and BPV-2 DNA in 57% of normal equine skin and dermatitis samples, indicating probable host-adapted strains, 1,2 FeSarPV was not detected in 120 samples of nonsarcoid feline samples of skin. 10 However, this cannot currently be ruled out in the affected lions, as no nonlesional skin was analyzed for FeSarPV, but it seems unlikely. A previous case report identified a similar, but not identical PV from a sarcoid in a mountain lion, 15 suggesting it is possible that 2 PVs can cause sarcoids in felids, however a different PV gene (E1) was sequenced in this case.…”
Section: Discussionmentioning
confidence: 99%
“…FJ977616). 10 The minor variation within the sequences was attributed to errors during sequencing rather than the presence of multiple PV variants.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation